Strategic risk management: the case of Northern Rock - McConnell, Patrick (Henry Stewart Talks, 2018)
Northern Rock PLC, Nationalisation of Northern Rock, High-risk business strategy, Financial crisis 2007, History of Northern Rock, Securitisation markets, Liquidity crisis, Northern Rock’s growth strategy, Strategic risk, Strategic risk management